Pelatihan Pembuatan Laporan Keuangan Sederhana UMKM Menggunakan Ms. Excel Tahun 2010 Pada Toko Dunia Plastik Kota Bengkulu - Noviantoro, Rinto; Putri, Sonalia Antama; Tarnia, Teni; Arthana T, Yosi (Universitas Dehasen Bengkulu, 2022)
Micro, Small and Medium Enterprises with abbreviations commonly known as MSMEs are a type of business or business entity that is real and contributes to the economy. MSMEs are now directed to be able to make improvements in recording good financial statements. Recording financial statements is one of the important factors in a business. Financial reports are useful for presenting financial information which is of course used for both internal and external parties related to these business activities. However, in reality there are still many MSMEs that have not reported financial statements for various reasons. On this occasion we would like to provide training on how to create or compile a simple financial report on Ms. Excel is easily accessible by business owners, one of which is at Toko Dunia Plastik, Bengkulu City. We see that Toko Dunia Plastik uses financial reports manually and does not yet have good and correct financial reports according to Financial Accounting Standards, which have not separated financial statements between capital, expenses, and private interests. Based on these problems and with the results of observations, we are moved to carry out socialization related to the preparation of financial reports so that they are easy to apply among MSMEs, especially the World Plastic Store.